Evaluation of relative tectonic perturbations of the Kashmir Basin, Northwest Himalaya, India: An integrated morphological approach. (15th October 2017) - Dubey, R.K.; Dar, Javid Ahmad; Kothyari, Girish Ch.
Graphical abstract: Highlights: The morphotectonics of the Kashmir Basin is established through analysis of River patterns. Relative Index of Active Tectonics (RIAT) is determined by simulation of different morphometric indices. The four evolutionary stages of the basin is established by simulation of different morphological parameters. The basin is categorized by different active tectonic classes. Abstract: Geomorphic and morphotectonic evaluations of the Kashmir Basin have been carried by implicating different geomorphic indices such as stream-gradient index (SL), hypsometric integral (HI), drainage basin asymmetry (AF), valley floor height and width ratio (Vf), transverse topographic symmetry factor (T), mountain front sinuosity (Smf), drainage basin shape (BS) and sinuosity index (SI) for the categorization of relative index of active tectonics (RIAT) through the use of geographic information systems (GIS) so as to decipher the role of neotectonics in geomorphologic evolution of the basin. The verified RIAT classes through field investigation and validation reveal the traverse of twenty-one active faults in the basin with demarcation of three RIAT classes viz., class-1 (inactive 20.07% of the area), class-2 (moderately active; 36.52% of the area) and class-3 (very active; 43.4% of the area). The observed values of RIAT distribution pattern are well corroborated with field observations. Ultimately, the overall geomorphic outputs and clustering of recent seismicity support the active tectonic control over the Kashmir basin, India.